Proyecto de regionalización SAP Business Objects - Cuneo Colina, Luis Alberto (2018)
The main objective of the project of a transnational company whose main business is the manufacture and commercialization of beer, was the standardization of management reports for decision making in the areas of Sales, Distribution and Commercial Finance through a single platform for the exploitation of regional information for the countries of Peru and Colombia. The project lasted forty-two weeks and had a budget of eight million Nuevos Soles. Two important factors for the success of the project should be highlighted: the quality of the data and the compliance with the schedule during the testing stage. The result was the implementation of a single repository with integrated and consistent information, containing seventy-five management indicators, on which a total of sixty-four standardized management reports were built for both countries. This achievement allowed us to improve the decision-making process and thus improve business management. Additionally, as a lesson learned, it is important to ensure the full-time assignment of the entire project team, because the attention to other activities can have a negative impact on the time allocated to the projects.